ANALISIS HAMBATAN SISWA DALAM MENGONSTRUK MASALAH KONSTEKSTUAL BERDASARKAN KONEKSI MATEMATIS SISWA - Tasni, Nurfaida; Upu, Hamzah; Ikram, Muhammad; Rahman, Muhammad Syarifuddin (LPPM Universitas Bina Bangsa, 2025)
Many students experience difficulties in understanding and connecting mathematical concepts with real-life situations around them. This study aims to analyze the obstacles faced by students in constructing contextual mathematical problems based on their mathematical connections. Using a qualitative approach through literature review, this study identifies various challenges encountered by students, including limited conceptual understanding, difficulties in relating mathematical concepts to real-life situations, and an inability to transform concrete information into abstract mathematical models. The findings indicate that understanding mathematical connections is essential for enhancing students' abilities to solve context-based problems.